2006
DOI: 10.1002/cbic.200500454
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Mechanism of Bee Venom Phospholipase A2 Inactivation by Bolinaquinone

Abstract: The molecular basis of the inactivation of bee venom PLA2 by the marine natural product bolinaquinone (BLQ) was studied by several spectral techniques (CD, fluorescence, and NMR spectroscopy, mass spectrometry), biomimetic reactions, and molecular modeling. Our data suggest competitive inhibition based on a BLQ-PLA2 noncovalent molecular recognition. However, BLQ is also able to react selectively with Lys133 through conjugate addition followed by a beta elimination. The biological implications of both the cova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…As discussed previously, the quinone moieties may be the active part in Michael addition reactions that interfere with regulatory molecules in living cells. 15 In addition to the quinone moiety of corallidictyals A/B (4/5), the aldehyde moiety may play an important role in the cytotoxic activity of siphonodictyal G (11) as compared to siphonodictyol G (2).…”
Section: Resultsmentioning
confidence: 99%
“…As discussed previously, the quinone moieties may be the active part in Michael addition reactions that interfere with regulatory molecules in living cells. 15 In addition to the quinone moiety of corallidictyals A/B (4/5), the aldehyde moiety may play an important role in the cytotoxic activity of siphonodictyal G (11) as compared to siphonodictyol G (2).…”
Section: Resultsmentioning
confidence: 99%
“…Plants, mammals, snakes and bee venoms can be the source of PLA 2 and according to their cellular location, these enzymes can be classified as cytosolic (cPLA 2 ), calcium independent (iPLA 2 ) and secretory (sPLA 2 ) [5]. Considering the three types of PLA 2 mentioned, studies revealed that sPLA 2 is deeply involved in the inflammatory process of several conditions [3,6] such as rheumatoid arthritis, atherosclerosis, respiratory distress syndrome and septic shock [4,5,7]. Most precisely, sPLA 2 leads to the formation of lipid inflammatory mediators through its lipolytic activity and also by activation of iPLA 2 [7].…”
Section: Introductionmentioning
confidence: 98%
“…Arachidonic acid (AA) is among the free fatty acids released representing a possible store of energy [2] and being involved in the biosynthesis of prostaglandins, prostacyclins, thromboxanes and interleukins -eicosanoids, known as mediators of inflammation and signal transduction [2][3][4]. Plants, mammals, snakes and bee venoms can be the source of PLA 2 and according to their cellular location, these enzymes can be classified as cytosolic (cPLA 2 ), calcium independent (iPLA 2 ) and secretory (sPLA 2 ) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Following our on-going extensive investigation on the PLA 2 inactivation mechanism by anti-inflammatory marine natural products (Monti et al, 2004a,b;Monti et al, 2006;Monti et al, 2009), and attracted by the perspective of a rational design of novel inhibitors as new potential lead compounds against inflammation-related diseases (Guerrero et al, 2007;Aquino et al, 2008), we have investigated the molecular mechanism of sPLA 2 -IIA inhibition by BLQ. The opportunity of exploring the reactivity of the p-quinone systems in this biological context and the latest findings of an oncogenic action of PLA 2 in prostate cancer (Mirtti et al, 2009) offered further motivations for this project.…”
mentioning
confidence: 99%